MICHAEL J. KURTZ, Managing Archival and Manuscript Repositories - McClure, Susan (Archivaria, 2011)
Managing Archival and Manuscript Repositories. MICHAEL J. KURTZ. Chicago: Society of American Archivists, 2004. 254 p. ISBN 1-931666-09-1.